Is the cattle tick Rhipicephalus annulatus Say, 1821 reared on the rabbit? - Abdel-Shafy, Sobhy (J Parasit Dis, 2018)
The cattle tick Rhipicephalus annulatus Say, 1821 (Acari: Ixodidae) is the main tick species on cattle in Egypt. This study was designed to know the possibility of rearing R. annulatus on rabbits in order to obtaining an adequate tick number and maintaining this tick species in lab to the next generation. Additionally, a comparison was performed between some biological parameters in R. annulatus fed on rabbits with that fed on cows. Six New Zealand white rabbits were used as a lab animal for rearing R. annulatus. The animals were divided into two groups. The first (G1) included four rabbits and the second (G2) included two rabbits. In G1, larvae fed until to reach unfed adults those were detached, cleaned their mouth parts carefully and re-fed on another rabbit. In G2, larvae were maintained on rabbits until to the fully fed females dropped. Oviposion, hatchability and life cycle of R. annulatus fed on rabbits were recorded and compared with those fed on cows. Results showed that although the cattle tick R. annulatus is highly specific to cattle, it is possible reared on rabbit in limited scale. The larvae well developed on the same rabbit to nymphs and adults. In G2, a very few adults completed their feeding and laid very small egg mass, some of eggs failed to hatch and a few recorded hatchability percentage not more than 9.1% in comparing 98.3% in females fed on cow. In G1, the rearing technique led to slightly increase the egg mass and their hatchability that reached to 23.6% in comparing with the hatchability recorded in G2.